Behaviour change potential for energy saving in non-domestic buildings: Development and pilot-testing of a benchmarking tool. (January 2014) - Ucci, M; Domenech, T; Ball, A; Whitley, T; Wright, C; Mason, D; Corrin, K; Milligan, A; Rogers, A; Fitzsimons, D; Gaggero, C; Westaway, A
Due to recent studies and government policies, designers and facilities managers are becoming increasingly aware of the role of occupant behaviour in energy conservation in buildings. While the use of post-occupancy surveys and benchmark tools is widespread in the built environment, there is limited research on assessing environmental and energy saving behaviours – particularly in non-domestic buildings. This article focuses on the development and pilot-testing of a novel benchmarking tool for the assessment of behaviour change potential for energy saving in the workplace, with findings from an industrial case study comprising a manufacturing and office environment. Beyond the findings of the case study, the article aims to provide a methodological framework for an easy-to-use benchmarking tool of user-behaviour within the context of energy saving in factories and offices. Practical Implications: This article discusses the development and pilot-testing of a novel questionnaire-based benchmarking tool for the assessment of behaviour change potential for energy saving in office and industrial settings. Its application to a case-study from the manufacturing sector demonstrates that the tool is easy to use, and it provides valuable insights on areas for improvement in energy use within non-domestic buildings, with a focus on user behaviour and management approaches. The tool can be used in applied research, for example in intervention studies for comparison within the same organisation (before and after), and/or for benchmarking against the performance of similar organisations.